Magnetotransport in graphene and related two-dimensional systems - Huang, N (2016)
This thesis describes studies on two-dimensional electron gases (2DEG) in graphene and related 2D systems. Magnetotransport investigations specifically in graphene and its bilayer system are demonstrated in detail, while the experimental techniques presented in this thesis are widely applicable to a large variety of other 2D materials. Chapter 1 gives an introduction and motivation for the principal topic presented in this thesis, with a general introduction to carbon nano-materials and an overview of the current state of graphene-related research and technological development (RTD). Chapter 2 establishes a basic theoretical framework which is essential for interpreting the results presented in this thesis, starting with the crystal and electronic band structures of graphene and its bilayer, followed by high magnetic fields effects on transport properties in these 2D systems. Chapter 3 details the experimental methods directly related to the presented work. The next three chapters report experimental results of three specific magnetotransport studies. Chapter 4 reports the disorder effects on epitaxial graphene in the vicinity of the Dirac point. Quadratic increases of carrier densities with temperature are found to be due to intrinsic thermal excitation combined with electron-hole puddles induced by charged impurities. It is also shown that the minimum conductivity increases with increasing disorder strength, in good agreement with quantum-mechanical numerical calculations. Chapter 5 reports measurements of the quantum Hall effect in epitaxial graphene showing the widest quantum Hall plateau observed to date extending over 50 T, attributed to a magnetic field dependent charge transfer process from charge reservoirs with exceptionally high densities of states in close proximity to the graphene. Using a realistic framework of broadened Landau levels this process is modelled in excellent agreement with experimental results. In Chapter 6, energy relaxation of hot carriers in graphene bilayer systems is investigated from measurements on Shubnikovde Haas oscillations and weak localisation. The hot-electron energy loss rate follows the predicted T4 power-law at carrier temperatures from 1.4 up to about 100 K, due to electron-acoustic phonon interactions. Comparisons are made between graphene monolayer and bilayer systems and a much stronger carrier density dependence of the energy loss rate is found in the bilayer system. This thesis concludes with a summary of the most important findings of the topics that have been discussed. The significance and limitations of the present research are listed. Some suggestions and outlook are given for possible improvements and interesting areas of future research and development.